Performance analysis of bit error rate for free space optical communication with tip-tilt compensation based on gamma–gamma distribution - Wu, Hanling; Yan, Haixing; Li, Xinyang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
In this paper, the gamma – gamma probability distribution is used to model turbulent channels. The bit error rate (BER) performance of free space optical (FSO) communication systems employing on-off keying (OOK) or subcarrier binary phase-shift keying (BPSK) modulation format is derived. A tip-tilt adaptive optics system is also incorporated with a FSO system using the above modulation formats. The tip-tilt compensation can alleviate effects of atmospheric turbulence and thereby improve the BER performance. The improvement is different for different turbulence strengths and modulation formats. In addition, the BER performance of communication systems employing subcarrier BPSK modulation is much better than that of compatible systems employing OOK modulation with or without tip-tilt compensation.
Optica Applicata, Vol. 39, 2009, nr 3, s. 533-545
Keywords: optyka; free space optical communication; atmospheric turbulence; adaptive optics; bit error rate; tip-tilt compensation